Relationships between weaning weight, maternal weaning weight, and milk production in polled Hereford cattle - Glaze, J.B. Jr.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Performance data from a Polled Hereford herd selected for improved feed conversion were used to calculate a variety of genetic parameters. Heritabilities were .14 for weaning wt, .18 for maternal weaning wt., and .19 for milk production. The genetic correlations were –.10 between weaning weight and maternal weaning weight and 0 between weaning weight and milk production. However, the genetic correlation between maternal weaning weight and milk was . 99, indicating they are essentially the same trait. Milk EPDs published by most breed associations are calculate d as the maternal weaning weight. Our study strongly supports this method of estimating an animal's genotype for milk production.
Keywords: Beef; Weaning weight; Maternal weaning weight; Milk production; Heritabilities; Genetic correlations